Exploring the biochemical and nutra-pharmaceutical prospects of some Thymus species: a review - Anwar, Farooq; Mahrye; Khan, Rahim; Qadir, Rahman; Saadi, Sami; Gruczynska‐Sekowska, Eliza; Saari, Nazamid; Hossain Brishti, Fatema (John Wiley and Sons, 2024)
The Thymus genus includes various medicinal and aromatic species, cultivated worldwide for their unique medicinal and economic value. Besides, their conventional use as a culinary flavoring agent, Thymus species are well-known for their diverse biological effects, such as antioxidant, anti-fungal, anti-bacterial, anti-viral, anti-tumor, anti-inflammatory, anti-cancer, and anti-hypertensive properties. Hence, they are used in the treatment of fever, colds, and digestive and cardiovascular diseases. The pharmaceutical significance of Thymus plants is due to their high levels of bioactive components such as natural terpenoid phenol derivatives (p-cymene, carvacrol, thymol, geraniol), flavonoids, alkaloids, and phenolic acids. This review examines the phytochemicals, biological properties, functional food, and nutraceutical attributes of some important Thymus species, with a specific focus on their potential uses in the nutra-pharmaceutical industries. Furthermore, the review provides an insight into the mechanisms of biological activities of key phytochemicals of Thymus species exploring their potential for the development of novel natural drugs.